2021
DOI: 10.1096/fj.202002394r
|View full text |Cite
|
Sign up to set email alerts
|

Moderate aerobic exercise training ameliorates impairment of mitochondrial function and dynamics in skeletal muscle of high‐fat diet‐induced obese mice

Abstract: The purpose of this study is to determine whether moderate aerobic exercise training improves high-fat diet-induced alterations in mitochondrial function and structure in the skeletal muscle. Male 4-week-old C57BL/6 mice were randomly divided into four groups: control (CON), control plus exercise (CON + EX), high-fat diet (HFD), and high-fat diet plus exercise (HFD + EX). After obesity was induced by 20 weeks of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
7
12
1
Order By: Relevance
“…In addition, the HFHC+EX increased fusion proteins (Mfn1) and reduced fission protein (Fis1) than the HFHC. Parallel results were observed by other studies, which investigated the expression of Mfn1 and Mfn2 in skeletal muscle tissues in animal [ 63 ] and human models [ 64 ]. The underlying mechanism of the effects of exercise training on mitochondria in the lung cells is complicated.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the HFHC+EX increased fusion proteins (Mfn1) and reduced fission protein (Fis1) than the HFHC. Parallel results were observed by other studies, which investigated the expression of Mfn1 and Mfn2 in skeletal muscle tissues in animal [ 63 ] and human models [ 64 ]. The underlying mechanism of the effects of exercise training on mitochondria in the lung cells is complicated.…”
Section: Discussionsupporting
confidence: 87%
“…That study suggested that the HFD and low-intensity endurance training modulated mitochondrial dynamics, contributing to insulin sensitivity, whereas they failed to generate an additive effect on mitochondrial biogenesis. In line with the above, no change in the MFN1 protein levels were detected in male C57BL/6 mice (4-week-old) fed a HFD ( 74 ). However, MFN2 and OPA1 protein levels were assessed at a lower level in the HFD-fed mice ( 74 ).…”
Section: Dietssupporting
confidence: 82%
“…In line with the above, no change in the MFN1 protein levels were detected in male C57BL/6 mice (4-week-old) fed a HFD ( 74 ). However, MFN2 and OPA1 protein levels were assessed at a lower level in the HFD-fed mice ( 74 ). These findings suggest that moderate aerobic training can only mitigate insulin resistance and mitochondrial dysfunction that are induced by obesity.…”
Section: Dietssupporting
confidence: 82%
“…The etiology of lung cancer is still not completely clear at present, and a large amount of data indicate that its pathogenic factors mainly include smoking, occupational exposure, air pollution, ionizing radiation, dietary habit, genetics, history of lung diseases, and so on. For the patients with medium and advanced lung cancer, the radiochemotherapy is an indispensable treatment, but it tends to cause nausea, vomiting, pain, fatigue, reduced physical activity endurance and other adverse symptoms, and affect the patients' respiratory system, resulting in the deterioration of their quality of life [ 2 , 3 ]. Therefore, effective nursing and rehabilitation training, along with the treatment, are needed to be given to the patients to relieve their clinical symptoms and improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%